The Possibility of Phenomenological Reduction - Zalewski, Andrzej (Hybris, 2012)
Historical arguments against the Husserlian phenomenological reduction stem from two mutually independent sources. First, some adherents of the so called realistic phenomenology understand the reduction as the rejection of the belief in the autonomous world’s existence, and this view seems untenable to them. Second, for some proponents of Heidegger’s philosophy from Sein und Zeit period reduction means disentanglement of the human being from the world, which is quite impossible. The article touches only the first group of these arguments (the second one is the theme of another paper). But, first of all, contrary to the common anti‑reductionist stance, the author states that the reduction is a performable procedure. He also considers reduction to be the wide‑spread operation of the Western philosophy, though being practised without the explicit knowledge concerning it.